The Role of LMKN (National Collective Management Board) in Fulfilling the Economic Rights of Music and Song Job Creation According to PP No. 57/2021 (A Studi in Medan) - Abdul Hadi Abdillah (International Journal of Economic, Technology and Social Sciences (Injects), 2023)
Copyright protection, especially for music or song creations, is a serious problem, because Indonesia is categorized as one of the countries where the level of copyright piracy is quite high. Even though there has been a law and a Collective Management Organization that has been formed specifically to deal with royalties for music and song creators, until now the level of royalty payments, especially in the city of Medan, is still low. Signs of improvement for the future of those who choose their livelihood as creators, musicians, singers are yet to be seen.